Effects of phosphodiesterase-5 inhibition with sildenafil on calcium waves in cardiac myocytes. (23rd February 2017) - Hutchings, David; Dibb, Katharine; Eisner, David; Trafford, Andrew
Abstract: Background: Diastolic Ca 2 + waves in cardiac myocytes lead to arrhythmias by inducing delayed after-depolarisations. Waves occur when sarcoplasmic reticulum (SR) content reaches a threshold level. The phosphodiesterase-5 inhibitor, sildenafil, is antiarrhythmic in mammalian myocardial ischaemia models, and in rat myocytes it reduces Ca 2 + transient amplitude and SR Ca 2 + content. We sought to determine effects of sildenafil on propensity to Ca 2 + waves in the large mammal. Methods: Sheep ventricular myocytes were voltage clamped and Ca 2 + fluorescence measured using fura-2. Cells were paced at 0·5 Hz with depolarisations from −40mV to +10mV. When at steady state, waves were induced with 7·5–15 mM Ca 2 + . Upon regular waving, sildenafil (1 μM) was applied. To determine threshold SR Ca 2 + content, caffeine (10 mM) was added immediately after a wave, and both wave and caffeine-induced Na + /Ca 2 + exchanger current ( I NCX )were integrated. Findings: Increasing external Ca 2 + increased SR content and induced diastolic waves. Sildenafil abolished waves in seven of 11 cells. In cells where sildenafil terminated waves, SR content was reduced below threshold. In addition, sildenafil treatment was associated with reduced rate constant of SERCA (kSERCA −68·4% of control, p<0·0001), initial (first 4 s) increase in sarcolemmal efflux via I NCX tail current (+190%, p=0·022), and reduced sarcolemmal influx via L-type Ca 2 + current ( I Ca-L ) (−29·8%, p=0·0015). In cells continuing to wave in sildenafil, SR threshold for waves was unchanged (123·8 μmol/L sildenafil vs 150·7, p=0·57). In unstimulated cells spontaneously waving in 10–15 mM Ca 2 +, sildenafil reduced wave frequency (6·3 waves per 20 s vs 2·7, p=0·0034). The effect of sildenafil on both wave models was abolished when cells were preincubated with the protein kinase G inhibitor, KT5823. Interpretation: Sildenafil suppresses waves induced by elevated external Ca 2 + via a protein kinase G-dependent mechanism. This suppression is mediated by reduced SR content, which itself is caused by reduced SERCA function and possible reduced I Ca-L . These findings highlight novel antiarrhythmic properties of phosphodiesterase-5 inhibition. Funding: British Heart Foundation.